ESTIMATIVA DE PARÂMETROS GENÉTICOS E MAPEAMENTO MOLECULAR DE QRLs À ANTRACNOSE DO COLMO EM MILHO TROPICAL - Tasior, Daniele (2014)
The study aimed to characterize the resistance of F2:3 progenies of maize inoculated with Colletotrichum graminicola, genetic parameters and map genomic regions associated with quantitative resistance alleles to anthracnose stalk in tropical maize determining the effects of each locus on resistance/susceptibility C. graminicola. Individuals of the F2 generation were selfed to generate F2:3 progenies, which were evaluated phenotypically for resistance to anthracnose stalk in three experiments. The treatments were consisted of 121 F2:3progenies, parental lines (L04-2 and L99-4) and the F1 generation, which were used as control. The experimental plots were arranged in a randomized block design with three replications. Each plot consisted in one row of 3 m in length with rows spaced 0.90 m apart, with a total of 15 plants per plot. The plants were inoculated in the anthesis stage by injecting 1 mL of spore suspension into the first or second elongated internode above ground. The data was collected 30 days after inoculation by evaluating the internal lesion length (CINT), external lesion length (CEXT) in cm and the number of discolored internodes (INT). From the phenotypic evaluations of 121 F2:3 progenies genetic parameters were associated with resistance to all three forms of assessment (CINT, INT and CEXT) in each experiment. The association of microsatellites and AFLP markers to resistance alleles was performed using multiple regression. AFLP and SSR loci used to form the construction of the linkage map by MAPMAKER version 3.0. Detection of the QRL was performed by composite interval mapping method using QTLCartographer program. The experimental results showed the existence of high genetic variability among the F2:3 progenies for resistance/susceptibility to C. graminicola. The forms of assessment of anthracnose stalk (CINT, INT and CEXT) were equally effective in discriminating susceptible from resistant individuals. The high broad-sense heritability confirms the great contribution of genetic variance for resistance, which ensures genetic gain for artificial selection in this pathosystem. The AFLP marker E55534 individually explained the greatest proportion of the phenotypic variation for the internal length (- 28.43%), external lesion length (- 27.70%) and the number of discolored internodes (- 27.45%) in F2:3 progenies of maize. The composite interval mapping identified 31 QRLs to anthracnose stalk segregating in the mapping population, which were mapped across the 10 linkage groups. This is the first report of the QRL to anthracnose stalk mapped on chromosomes 2, 3 and 10. At large number of mapped QRL is suggested that the inheritance of resistance in this tropical germplasm is more complex, conditioned by a large number of genes, some large phenotypic effects and the vast majority with small effects for resistance in this pathosystem.